Primary patency rate of Arteriovenous Fistula (AVF) and factors affecting its patency among Malaysian - Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal; Kasian, Junaini; Che Zan, M Sallehudin; Ahmed Ali, Ismail (IIUM Press, International Islamic University Malaysia, 2017)
The purpose of this study was to compare the maturity and patency rate of AVF being created at our centre in comparison to those being published elsewhere in the world. We are also analyzing different factors identified previously that may have affected this maturity and patency rate. This is an observational cross sectional study including all patients underwent AVF creation between 1st of January 2013 to 31st December 2013. We analysed non-modifiable factors including age, gender, presence of diabetes, presence of peripheral vascular disease and venous and artery diameter, and modifiable factors including smoking status, BMI index, anti-platelets and statin therapy and the site and side of AVF created, against the maturity and patency rate using a multi variates analysis. Our maturity rate at 6 weeks is 89% and patency rate at 6 months is 61% and at 12 months is 57%. Although there was a positive trends towards a better maturity rate in those who were treated with statin and with a bigger venous diameter, this was not statistically significant and these trends fail to sustain towards patency rates at both 6 and 12 months. In conclusion, our centre’s autologous AVF creation has been equally successful in comparison to other published results worldwide. Our study population failed to show any relationship between some known risk factors that has been shown by earlier study to have an effect on autologous AVF maturity and patency